Communication and change, the last ten years-and the next (University Press of Hawaii, 1976)
This framework combines the latest thinking from a number of fields in new ways. It critiques dominant instrumental, accountability-based approaches to development and evaluation and offers an alternative holistic, participatory, mixed methods approach based on systems and complexity thinking and other key concepts. It maintains a focus on power, gender and other differences and social norms.